DESIGN OF WEB-BASED DAILY REPORT APPLICATION FOR ACEH REGIONAL POLICE ICT FIELD USING DEVOPS METHOD - Muksalmina, Reza; Islamadina, Raihan; Aziz, Aulia Syarif; Dewi, Sarini Vita (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The advancement of information technology has driven the digitalization of administrative systems in various institutions, including law enforcement agencies. Currently, the daily reporting process at POLDA Aceh is still conducted manually, leading to issues such as delays, data inaccuracies, and difficulties in inter-unit coordination. This study aims to design and develop a web-based daily report application to enhance efficiency, transparency, and accountability in reporting. The DevOps methodology is applied in the development of this application to integrate the development and operational processes more efficiently. The use of PHP, MySQL, and CSS-based technology enables key features such as an interactive dashboard, digital report forms, advanced search and filtering, and account and unit management. A CI/CD (Continuous Integration/Continuous Deployment) pipeline is implemented to accelerate system updates and ensure application stability through automated testing and real-time performance monitoring. Testing results indicate that this application significantly improves reporting speed, minimizes recording errors, and facilitates better data access and management. The implementation of this system has positively impacted the operational effectiveness of POLDA Aceh, particularly in enhancing data-driven law enforcement services. Thus, this web-based daily report application is expected to serve as an innovative solution for digitalizing the reporting system within the police force.